2021
DOI: 10.1089/lgbt.2020.0128
|View full text |Cite
|
Sign up to set email alerts
|

Facial Masculinization from Procedures to Payment: A Review

Abstract: As the demand for gender-affirming procedures continues to increase, patients and providers have a greater imperative to understand the current state of facial masculinization. Facial reconstruction for transgender women has been shown to treat gender dysphoria effectively and reduce rates of discrimination and victimization. Although facial masculinization surgery for transgender men is less common, there are multiple surgical and nonsurgical options to supplement the effect of hormone therapy on facial appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Traditionally, sex is seen as innate and immutable, but newer arguments focus on sex as mutable and modifiable through surgery. 21 The ambiguous definitions of sex and medical necessity are what allow insurance companies to deny coverage for FGASs. An extensive review of FGAS across private and public insurance providers across the United States showed that coverage is extremely restricted in all but 3 states' Medicaid policies and the largest commercial insurance providers; they do not classify FGAS as medically necessary but as "cosmetic."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, sex is seen as innate and immutable, but newer arguments focus on sex as mutable and modifiable through surgery. 21 The ambiguous definitions of sex and medical necessity are what allow insurance companies to deny coverage for FGASs. An extensive review of FGAS across private and public insurance providers across the United States showed that coverage is extremely restricted in all but 3 states' Medicaid policies and the largest commercial insurance providers; they do not classify FGAS as medically necessary but as "cosmetic."…”
Section: Discussionmentioning
confidence: 99%
“…The legal definition of sex currently influences the medical treatment of patients that are transgender. Traditionally, sex is seen as innate and immutable, but newer arguments focus on sex as mutable and modifiable through surgery 21 . The ambiguous definitions of sex and medical necessity are what allow insurance companies to deny coverage for FGASs.…”
Section: Discussionmentioning
confidence: 99%